Identification of a highly drought-resistant pp7l hda6 mutant - Xu, Duorong; Leister, Dario; Kleine, Tatjana (Frontiers in Plant Science, 2024)
Plants have developed efficient strategies to counteract drought stress, including stomata closure, significant changes in nuclear gene expression, and epigenetic mechanisms. Previously, we identified Arabidopsis thaliana PROTEIN PHOSPHATASE7-LIKE (PP7L) as an extrachloroplastic protein that promotes chloroplast development. In addition, it was shown that PP7L is involved in high light and salt tolerance. Here, we demonstrate that the pp7l mutant can withstand prolonged periods of drought stress. Interestingly, despite impaired growth under standard growth conditions, photosynthetic efficiency recovers in pp7l mutant plants experiencing drought conditions. To assess the (post)transcriptional changes occurring in the pp7l mutant under different durations of drought exposure, we used an RNA-sequencing technique that allows the simultaneous detection of organellar and nuclear transcripts. Compared with the previously reported drought-responsive changes in the wild type, the drought-responsive changes in organellar and nuclear transcripts detected in the pp7l mutant were negligible. Our analysis of the data generated in this study and review and analysis of previous literature motivated us to create a pp7l hda6 (histone deacetylase 6) mutant, which exhibits remarkable drought resistance. Notably, the growth penalty associated with pp7l was alleviated in the double mutant, ruling out a dwarf effect on the drought-tolerant trait of this genotype. Future studies may consider that multiple loci and factors are involved in stress resistance and explore combinations of these factors to create even more resilient plants.